Wybrane motywy na monetach włoskich z lat 1922–1943 jako przykład recepcji rzymskich motywów numizmatycznych. Wyrażanie nowych treści poprzez odwołania do tradycji - Włodzimierz Lajsner (Studia Antiquitatis et Medii Aevi Incohantis)
(Selected motifs on Italian coins from 1922–1943 as an example of the reception of Roman numismatic motifs. Expressing new content through references to tradition): This text is devoted to the phenomenon of the reception of iconographic motifs appearing on Italian coins from 1922–1943, which have analogies in Roman coinage. Iconographic motifs from Italian coins, despite their stylistic similarity to motifs from Roman coins, contain new elements that change the symbolic content. References to Roman patterns on Italian coins were not accidental and served to create the desired image of the country, which was often different from historical reality.